DEVELOPMENT OF MUSCLE FATIGUE EVALUATION USING SURFACE ELECTROMYOGRAPHY SIGNAL AND PARAMETRIC-DISTANCE METHOD - Yogie Hartanto, Dananjaya
The advances in technology is growing unstoppable and occurs in almost all fields. In health sector, a lot of studies and research was done concerning muscles. Muscle is a part of the human body that is important in supporting the movements and activities of life. An evaluation of muscle fatigue has been carried out in various countries over the past three decades using Surface electromyography (sEMG). sEMG covers the use of electronic devices to measure muscle energy, analyze data, and display the results. The use of sEMG is very popular because it is non-invasive and easy to use. Evaluation of muscle fatigue should be performed while the muscles are not in contraction, i.e., during muscle relaxation. This study described the data acquisition process, signal processing techniques and the results of evaluating muscle fatigue during muscles relaxation using Time Series Modeling and Parametric-Distance Method. The results of muscle fatigue evaluation include boxplots which visually provide an illustration of the parametric distance distribution, that is how close the data is compared to the reference data. Some of the muscles analyzed in this study included vastus medialis and vastus lateralis in the right and left thigh muscles, in one subject/volunteer. The results of data processing and analysis using Time Series Modeling and Parametric-Distance Method showed that this method is quite effective in expressing muscle fatigue. This method can be proposed to be used as a complementary method in evaluating muscle fatigue.